Scanning training for rehabilitation of visual field loss due to stroke: Identifying and exploring training tools in use. (August 2019) - Hazelton, Christine; Pollock, Alex; Walsh, Glyn; Brady, Marian C
Introduction: Visual field loss affects one fifth of stroke survivors, limiting daily activities and reducing quality of life. Scanning training is a commonly used intervention, but there is variation in how this is delivered. This study aimed to identify the scanning training tools used in Scotland and describe their training parameters, delivery and suitability for use with stroke survivors. Method: An email survey identified scanning training tools used in Scotland. Two expert panel meetings gained consensus on the motor, language and cognitive skills required to use each scanning training tool. Video capture techniques gathered objective measures of training parameters. Results: Ten scanning training tools were identified. These tools used four delivery methods: paper-based, computer software, web-based and specialised equipment. They aimed to improve reading, perception or general visual skills. Fast, saccadic eye movements were most frequently targeted: two interventions also encouraged head movements. Session duration, frequency and therapist support varied considerably. The level of motor, language and cognitive skills required for each tool was determined. Conclusion: Scanning training tools used in Scotland vary in delivery modality, functional abilities required for use and visual skills trained. This information will support clinical decision-making and inform future research on training effectiveness and feasibility.